2013
DOI: 10.1007/s00586-013-2734-4
|View full text |Cite
|
Sign up to set email alerts
|

Posterior second sacral alar iliac screw insertion: anatomic study in a Chinese population

Abstract: Objective To provide radiographic parameters for optimal placement of posterior second sacral alar iliac (S2AI) screw for instrumentation and fusion of scoliosis to the second sacral level in a Chinese population. Methods S2AI screw trajectories were mapped on threedimensional computed tomography (3DCT) reconstructions of 60 normal adult pelvises. 1 mm inferior and 1 mm lateral to the S1 dorsal foramen were chosen as the entry point, and ideal S2AI screw trajectories were explored by rotating and cutting the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
6
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 30 publications
(38 reference statements)
8
81
6
5
Order By: Relevance
“…CA presented signi cant differences between males and females. This result is consistent with a previous study from Zhu et al, a radiographic study assessing optimal S2AI screw placement and presented that CA in females have 4 to 5 degrees more caudal trajectory compared with males [15]. But a study from Shillingford showed there is no signi cant differences in the CA or MA between females and males [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CA presented signi cant differences between males and females. This result is consistent with a previous study from Zhu et al, a radiographic study assessing optimal S2AI screw placement and presented that CA in females have 4 to 5 degrees more caudal trajectory compared with males [15]. But a study from Shillingford showed there is no signi cant differences in the CA or MA between females and males [2].…”
Section: Discussionsupporting
confidence: 92%
“…The average max-length of trajectory in females was approximately 8 mm shorter than that in males. Compared with previous study from Zhu et al [15], ML is different from their investigation in which the average max-length of trajectory in females was approximately 5 mm shorter than that in males. In clinical practice, the optional S2AI trajectory exceeds more the length of usually-used screw.…”
Section: Discussioncontrasting
confidence: 90%
“…The use of screws in the iliac bone reduces the incidence of these complications compared with the Galveston technique. However, the use of iliac screws may also present problems, the most common of which are screw prominence and surgical wound infection [5][6][7]. The S2AI fixation technique, originally described by Kebaish and Sponseller, reduces the incidence of these problems due to minimal dissection of soft tissues and an insertion point that is far from the skin, which facilitates the construction of the system since the entry point is aligned with the lumbar and S1 pedicular screws [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The studies describe a population comprised of 50% males and 50% females and demonstrate little difference between the sexes. [11][12][13] However, others showed that there are indeed anatomical differences between the sexes and between populations, [14][15][16][17] which justifies the development of studies in different populations in order to analyze the average anatomical parameters of each population group.…”
Section: Introductionmentioning
confidence: 99%